Synthesis, structural characterisation and cytotoxic study of multidentate dithiocarbazate schiff bases and their divalent Cu, Ni, and Zn complexes - Md Yusof, Enis Nadia (2014)
Three series of dithiocarbazate Schiff bases derived from S-benzyldithiocarbazate (SBDTC), S-2-methylbenzyldithiocarbazate (S2MBDTC) and S-4- methylbenzyldithiocarbazate (S4MBDTC) were synthesized using 2-hydroxy-3- methoxybenzaldehyde (OVa), 2-methoxybenzaldehyde (2MB), 3- methoxybenzaldehyde (3MB) and 2-furaldehyde (Fu) via condensation. The Schiff bases were then complexed with the respective metal salts to produce transition metal complexes. The metal complexes formed are expected to have a general formula of [M(ONS).H2O] and [M(NS)2] where M = Cu2+, Ni2+, and Zn2+. These compounds were characterized by elemental analysis, molar conductivity, magnetic susceptibility and various spectroscopic techniques including including Fourier-Transform Infrared (FT-IR), Nuclear Magnetic Resonance (NMR), Mass spectroscopy (MS), UltraViolet/Visible (UV/Vis) and Inductively Coupled Plasma – Atomic Emission Spectroscopy (ICP-AES) analyses. The elemental data obtained are in agreement with the proposed molecular formulae of Schiff bases and metal complexes. The complexes are non-electrolytes in DMSO solution, where anionic ligands are bonded covalently to the metal ions. The FTIR spectra of the dithiocarbazate Schiff bases displayed a sharp band which corresponded to v(C=N), that shifted to lower wavenumbers and a v(N-H) band which disappeared in all of the metal complexes suggesting the protonation of the Schiff bases that occurred upon complexation to the metal ions. The magnetic susceptibility measurements and spectral results support the coordination geometry in which the Schiff bases behave as tridentate ONS or bidentate NS donor ligand coordinating via the azomethine nitrogen, thiolo sulphur, and oxygen atoms (where applicable). Single crystal X-ray crystallographic analysis of seven new Schiff bases, one copper(II) complex, [Cu(S2MOVa).H2O].H2O, and one nickel (II) complex, Ni(SB3MB)2 were obtained. The Schiff bases and their metal complexes have been evaluated for their biological activities against an estrogen receptor positive breast cancer cell line (MCF-7) and an estrogen receptor negative breast cancer cell line (MDA-MB-231). All of the Cu(II) complexes showed marked cytotoxicity against cell lines while the other complexes were found to be inactive. The preliminary binding interaction of the copper(II) complexes with calf thymus DNA (CT-DNA) was also investigated and the binding constant (104-105 M-1) obtained indicate that the copper (II) complexes have a good binding affinity to the CT-DNA , in agreement with the cytotoxic data.